Knowledge and Practice on Rotacap Inhalation among Chronic Obstructive Pulmonary Disease Patients in a Teaching Hospital of Pokhara - Baral, Anisha; Gurung, Bishnu (NPRC Journal of Multidisciplinary Research, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a prevalent lung disease that causes restricted airflow and breathing difficulties. While COPD is incurable, proper management can help alleviate symptoms and improve patients' quality of life. Proper inhalation techniques, such as rotacap inhalation, play a crucial role in effective disease management. Objective: The study aimed to assess the knowledge and practice of rotacap inhalation among COPD patients at a teaching hospital in Pokhara. Methods: A descriptive cross-sectional research design was employed at Gandaki Medical College Teaching Hospital and Research Center, Pokhara. The study included 111 COPD patients who were present and willing to participate. Data were collected through a structured interview schedule and observation of practice using guidelines developed by CiplaMed. Data were entered and analyzed using SPSS version 16. Descriptive statistics, including frequency, percentage, mean, and standard deviation, were used, while inferential statistics (chi-square test) were applied at a 5% level of significance. Findings: The study revealed that only 18.9% of respondents had a good level of knowledge, while 28.8% demonstrated correct rotacap inhalation practice. Knowledge levels were significantly associated with age (p=0.003) and demonstration (p=0.005). Similarly, practice was significantly associated with age (p=0.002), religion (p=0.033), education (p=0.002), and demonstration (p<0.001). Furthermore, knowledge was significantly correlated with practice (p<0.001). Conclusion: The study concludes that although COPD patients had satisfactory knowledge, their practice of rotacap inhalation remained poor. This highlights the need for targeted educational interventions, including clear instructions and practical demonstrations, to enhance both knowledge and correct inhalation practices among COPD patients. Novelty: This study provides valuable insights into the gaps between knowledge and practice of rotacap inhalation among COPD patients in a teaching hospital setting. By identifying significant factors influencing knowledge and practice, the study underscores the necessity of structured educational programs to improve disease management.